Hubungan antara dukungan sosial dengan kemampuan interaksi sosial anak berkebutuhan khusus di SLB C Yakut Purwokerto - Hikmah Safitri; Umi Solikhah (Jurnal Keperawatan Muhammadiyah, 2020)
ABSTRACTBackground: Children with Special Needs is another term for "Disability Children" which indicates a special disorder. The social interaction ability of children with special needs is influenced by environmental factors, especially family, the role and involvement of parents. Social support is a form of attention, care, appreciation, comfort, calm or assistance given by others, both in groups and individually, especially for children with special needs despite limitations and developmental delays, but they also need to be valued, accepted and loved by the environment.Objective: To find the relation between social support and social interaction ability of children with special needs in SLB C Yakut Purwokerto.Method: This research uses quantitative description with cross sectional approach. Samples collected by total sampling were 79 respondents.Results: The results showed that the most of respondents were male 42 (53.2%), and majority were 10-year-old 19 (24.1%), with a form of mental retardation as much as 79 (100%). Disability children in SLB C Yakut Purwokerto who received good social support were 61 respondents (77.2%) and had good social interaction skills as many as 57 respondents (72.2%). The best form of social support was information support of 56 (76.7%).Conclusion: This study found significant improvement in social support towards the social interaction abilities of children with special needs.Keywords: Disability Children, Social Support, Social Interaction Capabilities